Bioprinting: A Tumor‐on‐a‐Chip System with Bioprinted Blood and Lymphatic Vessel Pair (Adv. Funct. Mater. 31/2019). (29th July 2019) - Cao, Xia; Ashfaq, Ramla; Cheng, Feng; Maharjan, Sushila; Li, Jun; Ying, Guoliang; Hassan, Shabir; Xiao, Haiyan; Yue, Kan; Zhang, Yu Shrike
Abstract : In article number1807173, Yu Shrike Zhang and co‐workers report the development of an improved tumor‐on‐a‐chip model consisting of a bioprinted hollow, perfusable blood vessel for liquid delivery and a hollow, single end‐blinded lymphatic vessel for interstitial fluid draining, hosted in a 3D tumor microenvironment‐like hydrogel matrix. This model featuring the biomimetic local microcirculation exhibits well‐controlled transport of biomolecules and anti‐cancer drugs.